Pembuatan Bilingual Guidebook oleh Mahasiswa Bahasa Inggris sebagai Upaya Penguatan Informasi Pariwisata Indonesia - Suharto, Ririn Pratiwi (Jurnal Bisnis Indonesia, 2024)
Students have an important role in Indonesia’s tourism sector. One way that can be done is to make areal contribution to tourism industry, such as providing information related to tourism. This effort wascarried out by English teachers through the English for Travel and Tourism course by designingproject-based learning that utilizes the use of English for tourism information needs by creating abilingual guidebook for tourist attractions. The aim of this research is to design a bilingual guidebookfor several places in Indonesia. The languages used are English and Bahasa Indonesia. This researchuses a project-based learning model, in which students are divided into four groups in one class tocarry out a project to make a bilingual guidebook. The research instruments are a project-basedlearning observation sheet and questionnaire of student perceptions in carrying out the project. Theresearch limitation is the selection of locations for the bilingual guidebook, including Sidoarjo,Surabaya, Tulungagung and West Nusa Tenggara. The location selection was based on theidentification of tourist attractions carried out by each group. The results of this research show thatthe use of English is applicable and the needs of the tourism industry are the design of four bilingualguidebooks containing tourism information, covering the areas of Sidoarjo, Surabaya, Tulungagungand West Nusa Tenggara. The implications of making a bilingual guidebook can be used as anEnglish learning model for the Tourism Industry. Apart from that, the bilingual guidebook can also beused for tourism information for readers.Keywords: Bilingual Guidebook; English; Tourism Information